Analisis Penggunaan Media Pembelajaran Braille Book KARTUNE sebagai Upaya Peningkatan Kepekaan Estetis Disabilitas Tunanetra - Adinda Kadwi L.P; Salha Hamidah; Ely Fiatus S.; Icha Silfia; Lutfi Mahmudah; Nur Fajrie (FKIP, Universitas Palangka Raya, 2024)
One of the physical limitations that attracts attention is blindness. In Indonesia, someone who experiences visual impairments is known as a blind person. This research focuses on PPSDSN Pendowo Kudus which is a Social Service Home for the Visually Sensory Disabled. Based on observations and interviews conducted by researchers regarding empowerment activities in the form of guidance at PPSDSN (Social Service Center for Visual Sensory Disabilities) Pendowo Kudus, data was obtained that the musical arts skills at PPSDSN Pendowo Kudus in their implementation experienced several obstacles including difficulties in memorizing the material and the unavailability of tutors since the start of the pandemic in 2019. Judging from the description that has been presented, the author attempts to provide a solution to this problem by proposing an idea for writing an article entitled